Building on the promise of diversity : how we can move to the next level in our workplaces, our communities, and our society - Thomas, R. Roosevelt (AMACOM, American Management Association, 2006)
"Building on the Promise of Diversity is Thomas's impassioned wake-up call to bring diversity management to a wholly new level - beyond finger-pointing and well-meaning "initiatives" and toward the shared goal of building robust organizations and thriving communities. This original, thoughtful, yet action-oriented book will help leaders in any setting - business, religious, educational, governmental, community groups, and more - break out of the status quo and reinvigorate the can-do spirit of making things better."--Jacket